2020
DOI: 10.1177/1533033820983290
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Factor 4 Is Involved in Papillary Thyroid Carcinoma via Regulating Long Non-Coding RNA HCP5

Abstract: The annual incidence of papillary thyroid carcinoma has increased dramatically. T cell factor 4 (TCF4) is an important component of Wnt signaling pathway.However, the role of TCF4 in PTC remains unknown. In this study, TCF4 was observed to overexpress in PTC patients and cells by qRT-PCR assay. The colony formation assay, Edu staining and transwell assay indicated thatoverexpression of TCF4 promoted cell proliferation and invasion of TCP-1 cells, whereas knockdown of TCF4 inhibited cell proliferation and invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
(42 reference statements)
0
2
0
Order By: Relevance
“…However, later a report showed an association between NLK (Nemo-like kinase), a member of the protein kinase (serine/threonine) superfamily, and TCF4 (T-cell factor 4), a transcription factor substrate for NLK in case of lung cancer that revealed that NLK expression was found to be negatively correlated with the expression of TCF4 in lung cancer advancement [ 93 ]. TCF-4, as a component of the Wnt pathway, also works as a tumor suppressor in colon cancer [ 94 ] and is involved in papillary thyroid carcinoma via regulation of HCP5 [ 95 ]. TBL1XR1 (Transducin (β)-like 1X related protein 1) is a subunit of SMRT/NCoR repressor complexes and is essentially required for activating signaling pathways [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, later a report showed an association between NLK (Nemo-like kinase), a member of the protein kinase (serine/threonine) superfamily, and TCF4 (T-cell factor 4), a transcription factor substrate for NLK in case of lung cancer that revealed that NLK expression was found to be negatively correlated with the expression of TCF4 in lung cancer advancement [ 93 ]. TCF-4, as a component of the Wnt pathway, also works as a tumor suppressor in colon cancer [ 94 ] and is involved in papillary thyroid carcinoma via regulation of HCP5 [ 95 ]. TBL1XR1 (Transducin (β)-like 1X related protein 1) is a subunit of SMRT/NCoR repressor complexes and is essentially required for activating signaling pathways [ 96 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, TCF4 inhibition represses cell proliferation and invasion but promotes cell cycle arrest and cell apoptosis in glioma (35). Moreover, in thyroid cancer, TCF4 binds to the promoter of lncRNA HLA complex P5 (HCP5) and activates HCP5 expression to facilitate cancer cell proliferation (36). Although TCF4 overexpression has previously been reported in thyroid cancer (34), the underlying mechanism that regulates its expression is unknown.…”
Section: Discussionmentioning
confidence: 99%